Silicon carbide porous ceramic and its preparation method and application

The method of slurry coating and template replication with in-situ silicon carbide whiskers and rare earth silicate coating addresses the mechanical and thermal shock issues of silicon carbide ceramics, resulting in high-strength, high-performance silicon carbide ceramics for high-temperature applications.

CN117003580BActive Publication Date: 2024-12-17WUHAN UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202310968180.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2024-12-17
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

Existing silicon carbide porous ceramics have poor mechanical properties and thermal shock resistance, making them unsuitable for high-temperature applications due to surface defects, irregular pore structures, and high preparation costs.

Method used

A method involving slurry coating and template replication using a 3D printed paraffin or organic polymer template, followed by sintering, to create a three-layer structure with in-situ silicon carbide whiskers and rare earth silicate coating, enhancing mechanical properties and thermal shock resistance.

Benefits of technology

The method produces silicon carbide porous ceramics with high strength, excellent thermal shock resistance, and resistance to high-temperature water vapor corrosion, suitable for environments up to 2200°C, with a simple and cost-effective process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117003580B_ABST
    Figure CN117003580B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of porous medium materials, and provides a silicon carbide porous ceramic and a preparation method and application thereof. The method comprises the following steps: impregnating a mesh porous template in a silicon carbide slurry, and sintering to obtain a silicon carbide preform; impregnating the silicon carbide preform in a rare earth slurry to obtain a silicon carbide porous ceramic body; and sintering the silicon carbide porous ceramic body under a protective atmosphere to obtain a silicon carbide porous ceramic. The present invention has the characteristics of simple process and low cost. The manufactured product has high strength at room temperature, high strength at high temperature, excellent thermal shock resistance, and good resistance to high temperature water vapor corrosion, and can be applied to a combustion environment of 1600 to 2200°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of porous medium materials, and in particular to a silicon carbide porous ceramic and a preparation method and application thereof. Background Art

[0002] Porous media combustion technology (PMC) is a new type of combustion technology developed by filling porous media in the combustion device to achieve effective utilization of gas fuel and clean and efficient combustion of low calorific value gas. It has self-heat storage capacity and "super-adiabatic" combustion characteristics, so it is widely used in metallurgy, internal combustion engines, gas turbines, micro-combustion systems and household heat exchangers. However, porous media combustion technology has not been widely used in high-temperature fields, mainly because of the lack of high-performance porous media materials for high-temperature environments. The current porous media materials generally have poor thermal shock resistance and are easily damaged during the frequent start-up and shutdown of the burner, resulting in a low service life of the burner. Therefore, improving the thermal shock resistance of porous media materials is the key to realizing the large-scale application of porous media combustion technology in high-temperature fields.

[0003] Silicon carbide porous ceramics have become high-quality materials for high-temperature porous media combustion technology due to their advantages such as low thermal expansion coefficient, high thermal conductivity and good thermal shock resistance. However, the silicon carbide porous ceramics prepared by the traditional slurry method have a large number of surface defects and hollow pore ribs formed due to the decomposition of the template skeleton at high temperature, resulting in low strength and thermal shock resistance. At present, technicians have conducted in-depth research and technological development to solve the problems of poor mechanical properties and thermal shock resistance of silicon carbide porous ceramics. For example, Chinese patent CN102503521A discloses a method for preparing high-strength silicon carbide porous ceramics, by adding aluminum disilicide and polycarbosilane to silicon carbide powder, dry pressing and two-step sintering to obtain high-strength silicon carbide porous ceramics. The added aluminum disilicide can promote the growth of silicon carbide grains, and polycarbosilane can form pores appropriately to control the porosity of the material. However, this technology needs to be sintered at a high temperature of 2200°C, and the powder needs to be dry-pressed at 50MPa, which not only consumes a lot of energy, but also has a relatively complicated process, which greatly increases the preparation cost of silicon carbide porous ceramics; in addition, the porosity of the prepared silicon carbide porous ceramics is only 55%, and the pores formed after foaming are mainly closed pores, which are difficult to form pores with a three-dimensional through-hole structure, and are not suitable as porous medium materials for high-temperature porous medium combustion. For example, Chinese patent CN110935237A discloses a multi-level porous silicon carbide porous ceramic for high-temperature flue gas filtration and a preparation method thereof, which prepares silicon carbide porous ceramics by an organic foam impregnation method by introducing elemental silicon alumina powder and aluminum sol into silicon carbide slurry. Although the organic foam impregnation method adopted by this technology is simple in process, it is difficult to control the thickness and porosity of the silicon carbide skeleton, and it is easy to cause pore blockage. In addition, the template used in this technology is a polyurethane sponge template with disordered pores. The irregular arrangement of pores will cause stress concentration and reduce the mechanical properties of silicon carbide porous ceramics. At the same time, after the template is burned out, vacuum holes will be left and defects will be formed on the surface of the skeleton, resulting in poor mechanical properties and thermal shock resistance, which cannot meet the requirements of high-temperature porous medium combustion.

[0004] Therefore, it is of great significance to provide a silicon carbide porous ceramic with excellent performance that can be applied to porous media combustion technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a silicon carbide porous ceramic and a preparation method and application thereof.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a silicon carbide porous ceramic, comprising the following steps:

[0008] (1) dipping the mesh porous template into silicon carbide slurry and sintering to obtain a silicon carbide preform;

[0009] (2) immersing the silicon carbide preform in a rare earth slurry to obtain a silicon carbide porous ceramic body;

[0010] (3) Sintering the silicon carbide porous ceramic body under a protective atmosphere to obtain the silicon carbide porous ceramic.

[0011] Preferably, the silicon carbide slurry in step (1) comprises silicon carbide, silicon powder, elemental silicon, phenolic resin, iron oxide, graphite, polycarboxylate, carboxymethyl cellulose and water;

[0012] The mass ratio of silicon carbide, silicon powder, elemental silicon, phenolic resin, iron oxide, graphite, polycarboxylate, carboxymethyl cellulose and water is 71-90: 3-6: 3-9: 2-8: 1-3: 1-3: 0.1-0.5: 0.2-0.9: 30-40.

[0013] Preferably, the polycarboxylate is ammonium polycarboxylate;

[0014] The average particle size of silicon carbide is ≤70 μm, the average particle size of silicon powder is ≤0.5 μm, the average particle size of elemental silicon is ≤50 μm, the average particle size of phenolic resin is ≤80 μm, the average particle size of iron oxide is ≤50 nm, and the average particle size of graphite is ≤20 μm.

[0015] Preferably, the immersion time in step (1) is 20 to 60 minutes;

[0016] The heating rate of the sintering is 1-3°C / min, the target temperature of the sintering is 1200-1600°C, and the holding time after reaching the target temperature is 0.5-3h.

[0017] Preferably, the rare earth slurry in step (2) comprises ytterbium oxide, samarium oxide, neodymium oxide, praseodymium oxide, silicon dioxide, carboxymethyl cellulose and water;

[0018] The mass ratio of ytterbium oxide, samarium oxide, neodymium oxide, praseodymium oxide, silicon dioxide, carboxymethyl cellulose and water is 22-26:20-22:19-21:19-21:10-20:0.5-1:23-46.

[0019] Preferably, the average particle size of ytterbium oxide, samarium oxide, neodymium oxide and praseodymium oxide is independently ≤1 μm, and the average particle size of silicon dioxide is ≤10 μm.

[0020] Preferably, the vacuum degree of the immersion in step (2) is 1000-2800 Pa, and the immersion time is 15-40 min.

[0021] Preferably, the heating rate of the sintering in step (3) is 2-5°C / min, the target temperature of the sintering is 1300-1600°C, and the holding time after reaching the target temperature is 1-5h.

[0022] The invention also provides silicon carbide porous ceramics obtained by the preparation method.

[0023] The invention also provides application of the silicon carbide porous ceramic in porous medium combustion technology.

[0024] The beneficial effects of the present invention are:

[0025] (1) The present invention provides a method for preparing silicon carbide porous ceramics, comprising the following steps: impregnating a mesh porous template in silicon carbide slurry and sintering to obtain a silicon carbide preform; impregnating the silicon carbide preform in a rare earth slurry to obtain a silicon carbide porous ceramic body; and sintering the silicon carbide porous ceramic body under a protective atmosphere to obtain a silicon carbide porous ceramic. The present invention has the characteristics of simple process and low cost. The manufactured product has high strength at room temperature, high strength at high temperature, excellent thermal shock resistance, and good resistance to high-temperature water vapor corrosion, and can be applied to a combustion environment of 1600 to 2200°C.

[0026] (2) The present invention adopts the coating of silicon carbide slurry, vacuum impregnation of rare earth silicate and high-temperature in-situ sintering technology. First, pre-sintering is performed in a carbon-buried atmosphere to form silicon carbide whiskers in situ in the silicon carbide skeleton. Then, the mixed slurry of rare earth oxide and silicon dioxide is infiltrated into the silicon carbide skeleton and adhered to the surface of the skeleton under a negative pressure environment by vacuum impregnation to fill the silicon carbide skeleton and repair defects. Finally, high-temperature sintering is performed in a protective atmosphere to form a silicon carbide whisker having a three-layer pore-rib structure (rare earth silicate ((Yb 0.25 Sm 0.25 Nd 0.25 Pr 0.25 )2SiO5) coating, silicon carbide skeleton layer and rare earth silicate ((Yb 0.25 Sm 0.25 Nd 0.25 Pr 0.25 )2SiO5) filling layer) of silicon carbide porous ceramics. Among them, the in-situ generation of silicon carbide whiskers can greatly improve the mechanical properties and thermal shock resistance of the prepared silicon carbide porous ceramics. Combined with the vacuum impregnation technology, a three-layer pore-rib structure is formed, and rare earth silicates ((Yb 0.25 Sm 0.25 Nd 0.25 Pr 0.25 )2SiO5) coating can also greatly improve the high temperature water vapor corrosion resistance of silicon carbide porous ceramics. High temperature synthesized equiatomic quaternary rare earth silicate ((Yb 0.25 Sm0.25 Nd 0.25 Pr 0.25 )2SiO5) Compared with single-component rare earth silicate, the high entropy design can reduce its linear expansion coefficient, making it better matched with the silicon carbide skeleton; and because the linear expansion coefficient of the rare earth silicate coating is slightly higher than that of the silicon carbide skeleton, residual compressive stress will be generated during the sintering process, further improving the mechanical properties of silicon carbide porous ceramics.

[0027] (3) The method used in the present invention to prepare the silicon carbide porous ceramics is a template replication method, which is to prepare the silicon carbide porous ceramics by slurry coating and template burning on the surface of a 3D printed paraffin, resin or organic polymer template. Compared with other methods for preparing porous materials, such as foaming molding, pore forming agents, hot pressing molding, etc., the template replication method involved in the present invention is simpler, lower in cost, and more efficient, and can be used on a large scale.

[0028] (4) The iron oxide added to the silicon carbide slurry reacts with CO in a carbon-buried atmosphere through a reduction reaction (1) to generate nano-iron, and then the iron forms a low eutectic phase with internal impurities to produce a liquid phase; at the same time, SiO2 reacts with C to generate SiO and CO vapor through a reaction (2); and then silicon carbide is generated through reactions (3), (4), and (5). The SiC generated during the reaction will first nucleate and crystallize along a direction that is conducive to its growth, and then be transported and adsorbed in the liquid phase to generate silicon carbide whiskers. In-situ silicon carbide whiskers can deflect cracks or hinder crack propagation through mechanisms such as pull-out and bridging interlocking, thereby greatly improving the strength and thermal shock resistance of silicon carbide porous ceramics.

[0029] Fe2O3(s)+3CO(g)→2Fe(s)+3CO2(g) ΔG 0 =-23470-353T (1)

[0030] SiO2(s)+C(s)→SiO(g)+CO(g) ΔG 0 =688354-344T (2)

[0031] SiO(g)+3CO(g)→SiC(s)+2CO2(g) ΔG 0 =-465568+379T (3)

[0032] SiO(g)+2C(s)→SiC(s)+CO(g) ΔG 0 =-132770+33.9T (4)

[0033] Si(s)+2CO(g)→SiC(s)+CO2(g) ΔG 0 =-240788-179.66T (5)

[0034] (5) During the vacuum impregnation process, the in-situ formation of silicon carbide whiskers is beneficial to the adsorption of vacuum impregnation slurry by silicon carbide porous ceramics, and the surface coating thickness is also significantly increased, which has a positive effect on the improvement of mechanical properties and thermal shock resistance. At the same time, the silicon carbide whiskers on the surface of the preform can inhibit the formation of cracks on the coating surface, and the pores on the coating surface are gradually repaired, which can further improve the strength and thermal shock resistance of silicon carbide porous ceramics. In addition, the rare earth silicate (Yb 0.25 Sm 0.25 Nd 0.25 Pr 0.25 The )2SiO5) coating has good resistance to high-temperature water vapor corrosion and can protect the silicon carbide substrate during service and increase its service life.

[0035] (6) The in-situ whisker network reinforced 3D printed silicon carbide porous ceramics prepared by the present invention have been tested to have the following characteristics: high temperature resistance (1600-2200°C), high strength (compressive strength at room temperature 2.8-6.4Mpa), good thermal shock resistance (3 water cooling cycles at 1100°C, residual strength retention rate of 80-95%), and good resistance to high temperature water vapor corrosion (used in a 1400°C water vapor environment for 1000h, weight gain of 0.6-2.1%). BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram of the structure of the silicon carbide porous ceramic in Example 1;

[0037] Figure 2 This is a SEM characterization image of the pore-rib fracture of the silicon carbide porous ceramic in Example 1 (1 is a high-entropy rare earth silicate coating, 2 is a silicon carbide skeleton layer, and 3 is a high-entropy rare earth silicate filling layer);

[0038] Figure 3 This is a SEM characterization image of the skeleton layer of the silicon carbide porous ceramic in Example 1;

[0039] Figure 4 This is a SEM characterization image of the coating surface of the silicon carbide porous ceramic in Example 1. DETAILED DESCRIPTION

[0040] The present invention provides a method for preparing a silicon carbide porous ceramic, comprising the following steps:

[0041] (1) dipping the mesh porous template into silicon carbide slurry and sintering to obtain a silicon carbide preform;

[0042] (2) immersing the silicon carbide preform in a rare earth slurry to obtain a silicon carbide porous ceramic body;

[0043] (3) Sintering the silicon carbide porous ceramic body under a protective atmosphere to obtain the silicon carbide porous ceramic.

[0044] In the present invention, the structure of the mesh porous template in step (1) is a three-dimensional ordered through-hole array, and the chemical composition of the mesh porous template is one or two of resin, paraffin or polyurethane.

[0045] In the present invention, the silicon carbide slurry in step (1) preferably comprises silicon carbide, silicon powder, elemental silicon, phenolic resin, iron oxide, graphite, polycarboxylate, carboxymethyl cellulose and water.

[0046] In the present invention, the mass ratio of silicon carbide, silicon powder, elemental silicon, phenolic resin, iron oxide, graphite, polycarboxylate, carboxymethyl cellulose and water is preferably 71-90: 3-6: 3-9: 2-8: 1-3: 1-3: 0.1-0.5: 0.2-0.9: 30-40, more preferably 75-85: 4-5: 5-8: 3-7: 1.5-2.5: 1.5-2.5: 0.2-0.4: 0.3-0.8: 32-38, and more preferably 77-80: 4.2-4.5: 6-7: 5-6: 1.7-2: 1.7-2: 0.25-0.3: 0.5-0.6: 35-36.

[0047] In the present invention, the graphite is preferably flake graphite or graphite oxide, and the polycarboxylate is preferably ammonium polycarboxylate.

[0048] In the present invention, the residual carbon content of the phenolic resin is preferably ≥40%, more preferably ≥42%, and even more preferably ≥45%.

[0049] In the present invention, the average particle size of silicon carbide is preferably ≤70μm, more preferably ≤68μm, more preferably ≤65μm; the average particle size of silicon powder is preferably ≤0.5μm, more preferably ≤0.3μm, more preferably ≤0.1μm; the average particle size of elemental silicon is preferably ≤50μm, more preferably ≤45μm, more preferably ≤40μm; the average particle size of phenolic resin is preferably ≤80μm, more preferably ≤78μm, more preferably ≤75μm; the average particle size of iron oxide is preferably ≤50nm, more preferably ≤45nm, more preferably ≤40nm; the average particle size of graphite is preferably ≤20μm, more preferably ≤18μm, more preferably ≤15μm.

[0050] In the present invention, the method for preparing the silicon carbide slurry preferably comprises the following steps: mixing silicon carbide, silicon powder, elemental silicon, phenolic resin, iron oxide and graphite to obtain a mixed powder; then adding polycarboxylate, carboxymethyl cellulose and water, stirring to obtain silicon carbide slurry.

[0051] In the present invention, the stirring speed is preferably 100-300 r / min, more preferably 150-250 r / min, more preferably 180-200 r / min; the stirring time is preferably 40-60 min, more preferably 45-55 min, more preferably 50-53 min.

[0052] In the present invention, the immersion time in step (1) is preferably 20 to 60 min, more preferably 30 to 50 min, and even more preferably 35 to 40 min.

[0053] In the present invention, after the impregnation in step (1) is completed, the template is taken out, squeezed or centrifuged, and then dried. After the drying is completed, sintering in step (1) is performed.

[0054] In the present invention, the drying temperature is preferably 60-90°C, more preferably 70-80°C, and more preferably 72-75°C; the drying time is preferably 24-48h, more preferably 30-42h, and more preferably 36-38h.

[0055] In the present invention, the sintering in step (1) is carried out in a carbon-buried atmosphere, and the heating rate of the sintering is preferably 1-3°C / min, more preferably 1.5-2.5°C / min, and more preferably 1.7-2°C / min; the target temperature of the sintering is preferably 1200-1600°C, more preferably 1300-1500°C, and more preferably 1350-1400°C; the holding time after reaching the target temperature is preferably 0.5-3h, more preferably 1-2.5h, and more preferably 1.5-2h.

[0056] In the present invention, the rare earth slurry in step (2) preferably comprises ytterbium oxide, samarium oxide, neodymium oxide, praseodymium oxide, silicon dioxide, carboxymethyl cellulose and water.

[0057] In the present invention, the mass ratio of ytterbium oxide, samarium oxide, neodymium oxide, praseodymium oxide, silicon dioxide, carboxymethyl cellulose and water is preferably 22-26:20-22:19-21:19-21:10-20:0.5-1:23-46, further preferably 23-25:20.5-21.5:19.5-20.5:19.5-20.5:11-19:0.6-0.9:29-40, and more preferably 23.5-24:20.7-21:19.7-20:19.7-20:13-15:0.7-0.8:33-35.

[0058] In the present invention, the average particle size of ytterbium oxide, samarium oxide, neodymium oxide and praseodymium oxide is independently preferably ≤1 μm, further preferably ≤0.8 μm, more preferably ≤0.5 μm; the average particle size of silicon dioxide is preferably ≤10 μm, further preferably ≤8 μm, more preferably ≤5 μm.

[0059] In the present invention, the method for preparing the rare earth slurry preferably comprises the following steps: mixing ytterbium oxide, samarium oxide, neodymium oxide, praseodymium oxide and silicon dioxide to obtain a mixed powder; then adding carboxymethyl cellulose and water, and ball milling to obtain a rare earth slurry.

[0060] In the present invention, the rotation speed of the ball mill is preferably 300-500 r / min, more preferably 350-450 r / min, more preferably 370-400 r / min; the time of the ball mill is preferably 1-4 h, more preferably 2-3 h, more preferably 2.2-2.5 h.

[0061] In the present invention, the vacuum degree of the immersion in step (2) is preferably 1000-2800 Pa, more preferably 1500-2300 Pa, and more preferably 1700-2000 Pa; the immersion time is preferably 15-40 min, more preferably 20-35 min, and more preferably 25-30 min.

[0062] In the present invention, after the impregnation in step (2) is completed, the obtained sample is dried to obtain a silicon carbide porous ceramic body.

[0063] In the present invention, the drying temperature is preferably 60 to 90° C., more preferably 70 to 80° C., and more preferably 72 to 75° C.; the drying time is preferably 12 to 24 h, more preferably 16 to 20 h, and more preferably 17 to 18 h.

[0064] In the present invention, the protective atmosphere in step (3) is preferably argon or nitrogen.

[0065] In the present invention, the heating rate of the sintering in step (3) is preferably 2-5°C / min, more preferably 3-4°C / min, and more preferably 3.2-3.5°C / min; the target temperature of the sintering is preferably 1300-1600°C, more preferably 1350-1550°C, and more preferably 1400-1500°C; the holding time after reaching the target temperature is preferably 1-5h, more preferably 2-4h, and more preferably 2.5-3h.

[0066] In the present invention, after the sintering in step (3) is completed, the furnace is cooled to obtain the silicon carbide porous ceramic.

[0067] In the present invention, the target temperature of the furnace cooling is preferably 20 to 30°C, more preferably 22 to 28°C, and even more preferably 23 to 25°C.

[0068] The invention also provides silicon carbide porous ceramics obtained by the preparation method.

[0069] The invention also provides application of the silicon carbide porous ceramic in porous medium combustion technology.

[0070] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0071] Example 1

[0072] 8.3 kg of silicon carbide with a particle size of 65 μm, 0.4 kg of silicon micropowder with a particle size of 0.5 μm, 0.3 kg of elemental silicon with a particle size of 40 μm, 0.6 kg of phenolic resin with a particle size of 75 μm (residual carbon content of 45%), 0.2 kg of iron oxide with a particle size of 45 nm and 0.2 kg of flake graphite with a particle size of 15 μm were mixed to obtain a mixed powder; then 0.03 kg of ammonium polycarboxylate, 0.05 kg of carboxymethyl cellulose and 4 kg of water were added to the mixed powder, and stirred at a speed of 200 r / min for 50 min to obtain a silicon carbide slurry;

[0073] 2.46 kg of ytterbium oxide with a particle size of 0.5 μm, 2.15 kg of samarium oxide with a particle size of 0.5 μm, 2.05 kg of neodymium oxide with a particle size of 0.5 μm, and 2.04 kg of praseodymium oxide with a particle size of 0.5 μm were mixed with 1.3 kg of silicon dioxide with a particle size of 5 μm to obtain a mixed powder, and then 0.05 kg of carboxymethyl cellulose and 3.5 kg of water were added to the mixed powder, and ball milled at a speed of 400 r / min for 2.5 hours to obtain a rare earth slurry;

[0074] The polyurethane was immersed in the silicon carbide slurry for 40 minutes, the template was taken out, the slurry was centrifuged, and then dried at 75°C for 36 hours. After drying, the temperature was increased to 1400°C at a heating rate of 2°C / min in a carbon-buried atmosphere, and the temperature was kept for 1.5 hours to obtain a silicon carbide preform;

[0075] The silicon carbide preform was immersed in the rare earth slurry, vacuumed to 2000Pa, immersed for 25 minutes, and after the immersion, the obtained sample was dried at 75°C for 18 hours to obtain a silicon carbide porous ceramic body;

[0076] In an argon atmosphere, the silicon carbide porous ceramic body was heated to 1400° C. at a rate of 3.5° C. / min, kept at that temperature for 2.5 hours, and then cooled to 25° C. in the furnace to obtain the silicon carbide porous ceramic.

[0077] The structural diagram of the silicon carbide porous ceramic in this embodiment is as follows: Figure 1 As shown; the SEM characterization of the pore-rib fracture of the silicon carbide porous ceramic in this embodiment, as Figure 2 As shown ( Figure 2 1 is a high entropy rare earth silicate coating, 2 is a silicon carbide skeleton layer, and 3 is a high entropy rare earth silicate filling layer); the skeleton layer SEM characterization of the silicon carbide porous ceramic in this embodiment is as shown in FIG. Figure 3 As shown; the SEM characterization of the coating surface of the silicon carbide porous ceramic in this embodiment, as shown Figure 4 As shown. Figures 1 to 4 It can be seen that after pre-sintering in a carbon-buried atmosphere, silicon carbide whiskers are formed in situ in the silicon carbide skeleton, and then the mixed slurry of rare earth oxides and silicon dioxide is infiltrated into the silicon carbide skeleton and adhered to the skeleton surface under a negative pressure environment by vacuum impregnation, filling the silicon carbide skeleton and repairing defects. Finally, a three-layer pore-rib structure (rare earth silicate ((Yb 0.25 Sm 0.25 Nd 0.25 Pr 0.25 )2SiO5) coating, silicon carbide skeleton layer and rare earth silicate ((Yb 0.25 Sm 0.25 Nd 0.25 Pr 0.25 )2SiO5) filling layer) of silicon carbide porous ceramics.

[0078] Performance testing of the silicon carbide porous ceramics obtained in this embodiment showed that the room temperature compressive strength of the silicon carbide porous ceramics in this embodiment was 2.8 MPa. It can be used normally for 10,000 hours at 2,200°C. After three water-cooling cycles at 1,100°C, the residual strength retention rate is 80%. After being used for 1,000 hours in a water vapor environment at 1,400°C, the weight increased by 2.1%.

[0079] Example 2

[0080] 8 kg of silicon carbide with a particle size of 68 μm, 0.42 kg of silicon micropowder with a particle size of 0.3 μm, 0.6 kg of elemental silicon with a particle size of 45 μm, 0.5 kg of phenolic resin with a particle size of 78 μm (residual carbon content of 42%), 0.17 kg of iron oxide with a particle size of 40 nm and 0.17 kg of graphite oxide with a particle size of 18 μm were mixed to obtain a mixed powder; then 0.025 kg of ammonium polycarboxylate, 0.06 kg of carboxymethyl cellulose and 3.6 kg of water were added to the mixed powder, and stirred at a speed of 180 r / min for 53 min to obtain a silicon carbide slurry;

[0081] 2.48 kg of ytterbium oxide with a particle size of 0.8 μm, 2.17 kg of samarium oxide with a particle size of 0.8 μm, 2.08 kg of neodymium oxide with a particle size of 0.8 μm, and 2.07 kg of praseodymium oxide with a particle size of 0.8 μm were mixed with 1.2 kg of silicon dioxide with a particle size of 8 μm to obtain a mixed powder, and then 0.07 kg of carboxymethyl cellulose and 3.3 kg of water were added to the mixed powder, and ball milling was performed at a speed of 370 r / min for 2.2 hours to obtain a rare earth slurry;

[0082] The resin was impregnated in the silicon carbide slurry for 50 minutes, the template was taken out, the slurry was centrifuged, and then dried at 80°C for 30 hours. After drying, the temperature was increased to 1350°C at a heating rate of 1.5°C / min in a carbon-buried atmosphere and kept at this temperature for 2 hours to obtain a silicon carbide preform;

[0083] The silicon carbide preform was immersed in the rare earth slurry, vacuumed to 2300Pa, immersed for 20 minutes, and after the immersion, the obtained sample was dried at 80°C for 16 hours to obtain a silicon carbide porous ceramic body;

[0084] In an argon atmosphere, the silicon carbide porous ceramic body is heated to 1500° C. at a rate of 3° C. / min, kept at this temperature for 2 hours, and then cooled to 30° C. in the furnace to obtain the silicon carbide porous ceramic.

[0085] Performance testing of the silicon carbide porous ceramics obtained in this embodiment showed that the room temperature compressive strength of the silicon carbide porous ceramics in this embodiment was 4.6 MPa. It can be used normally for 10,000 h at 2000°C. After three water-cooling cycles at 1100°C, the residual strength retention rate is 87%. After being used for 1000 h in a water vapor environment at 1400°C, the weight increased by 1.5%.

[0086] Example 3

[0087] 7.7 kg of silicon carbide with a particle size of 67 μm, 0.5 kg of silicon micropowder with a particle size of 0.1 μm, 0.9 kg of elemental silicon with a particle size of 42 μm, 0.7 kg of phenolic resin with a particle size of 77 μm (residual carbon content of 43%), 0.25 kg of iron oxide with a particle size of 47 nm and 0.3 kg of flake graphite with a particle size of 20 μm were mixed to obtain a mixed powder; then 0.05 kg of ammonium polycarboxylate, 0.07 kg of carboxymethyl cellulose and 3.2 kg of water were added to the mixed powder, and stirred at a speed of 150 r / min for 55 min to obtain a silicon carbide slurry;

[0088] 2.4 kg of ytterbium oxide with a particle size of 0.5 μm, 2.1 kg of samarium oxide with a particle size of 0.5 μm, 2.0 kg of neodymium oxide with a particle size of 0.5 μm, and 2.0 kg of praseodymium oxide with a particle size of 0.5 μm were mixed with 1.5 kg of silicon dioxide with a particle size of 5 μm to obtain a mixed powder, and then 0.08 kg of carboxymethyl cellulose and 4 kg of water were added to the mixed powder, and ball milling was performed at a speed of 350 r / min for 3 hours to obtain a rare earth slurry;

[0089] The paraffin was immersed in the silicon carbide slurry for 35 minutes, the template was taken out, extruded, and then dried at 90°C for 24 hours. After drying, the temperature was increased to 1300°C at a heating rate of 1°C / min in a carbon-buried atmosphere, and kept at this temperature for 2.5 hours to obtain a silicon carbide preform;

[0090] The silicon carbide preform was immersed in the rare earth slurry, vacuumed to 1500Pa, immersed for 20 minutes, and after the immersion, the obtained sample was dried at 90°C for 12 hours to obtain a silicon carbide porous ceramic body;

[0091] In a nitrogen atmosphere, the silicon carbide porous ceramic body was heated to 1350° C. at a rate of 5° C. / min, kept at that temperature for 4 hours, and then cooled to 20° C. in the furnace to obtain the silicon carbide porous ceramic.

[0092] The performance of the silicon carbide porous ceramics obtained in this embodiment was tested, and it was found that the room temperature compressive strength of the silicon carbide porous ceramics in this embodiment was 6.4 MPa. It can be used normally for 10000 h at 2100°C. After three water-cooling cycles at 1100°C, the residual strength retention rate is 95%. After being used for 1000 h in a water vapor environment at 1400°C, the weight increased by 0.6%.

[0093] Comparative Example 1

[0094] The other conditions in Example 1 remain unchanged, and the addition of iron oxide is abandoned to obtain a silicon carbide ceramic material.

[0095] The performance of the silicon carbide ceramic material obtained in this comparative example was tested, and the room temperature compressive strength of the silicon carbide ceramic material in this comparative example was found to be 1.6 MPa. After three water cooling cycles at 1100°C, the residual strength retention rate was 65%. After being used in a 1400°C water vapor environment for 1000 hours, the weight increased by 3.7%.

[0096] This is because no iron oxide was added in Comparative Example 1, and the number of silicon carbide whiskers generated was small, resulting in a low retention rate of compressive strength and residual strength.

[0097] Comparative Example 2

[0098] The other conditions in Example 1 are kept unchanged, and the addition of flake graphite is abandoned to obtain a silicon carbide ceramic material.

[0099] The performance of the silicon carbide ceramic material obtained in this comparative example was tested, and it was found that the room temperature compressive strength of the silicon carbide ceramic material in this comparative example was 1.4 MPa. After three water-cooling cycles at 1100°C, the residual strength retention rate was 58%. After being used in a 1400°C water vapor environment for 1000 hours, the weight increased by 4.2%.

[0100] This is because no graphite was added in Comparative Example 2, and the number of silicon carbide whiskers generated was also relatively small, resulting in lower compressive strength and residual strength retention rates.

[0101] Comparative Example 3

[0102] While keeping other conditions in Example 1 unchanged, the rare earth oxide and silicon dioxide in the rare earth slurry were replaced with a mixture of 3 kg of activated alumina powder and 7 kg of andalusite powder to obtain a silicon carbide ceramic material.

[0103] The performance of the silicon carbide ceramic material obtained in this comparative example was tested, and it was found that the room temperature compressive strength of the silicon carbide ceramic material in this comparative example was 2.5 MPa. After three water cooling cycles at 1100°C, the residual strength retention rate was 77%. After being used in a 1400°C water vapor environment for 1000 hours, the weight increased by 7.3%.

[0104] This is because the rare earth oxide-silicon dioxide powder is replaced by andalusite-alumina powder in Comparative Example 3, and the resulting mullite has better water vapor corrosion resistance than the silicate rare earth silicate (Yb 0.25 Sm 0.25 Nd 0.25 Pr 0.25 )2SiO5) is inferior, resulting in greater weight gain.

[0105] It can be seen from the above embodiments that the present invention provides a method for preparing silicon carbide porous ceramics, which has the characteristics of simple process and low cost. The manufactured products have high strength at room temperature, high strength at high temperature, excellent thermal shock resistance, good resistance to high-temperature water vapor corrosion, and can be suitable for combustion environments of 1600 to 2200°C.

[0106] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous silicon carbide ceramic, characterized in that: It includes the following steps: (1) dipping the mesh porous template into silicon carbide slurry and sintering to obtain a silicon carbide preform; (2) immersing the silicon carbide preform in a rare earth slurry to obtain a silicon carbide porous ceramic body; (3) sintering the silicon carbide porous ceramic body under a protective atmosphere to obtain the silicon carbide porous ceramic; The mesh porous template in step (1) is obtained by 3D printing, the structure of the mesh porous template is a three-dimensional ordered through-hole array, and the composition of the mesh porous template is one or two of resin, paraffin or polyurethane; The silicon carbide slurry in step (1) comprises silicon carbide, silicon powder, elemental silicon, phenolic resin, iron oxide, graphite, polycarboxylate, carboxymethyl cellulose and water; The mass ratio of silicon carbide, silicon powder, elemental silicon, phenolic resin, iron oxide, graphite, polycarboxylate, carboxymethyl cellulose and water is 71-90: 3-6: 3-9: 2-8: 1-3: 1-3: 0.1-0.5: 0.2-0.9: 30-40; The soaking time in step (1) is 20 to 60 minutes; The sintering in step (1) is carried out in a carbon-buried atmosphere, the heating rate of the sintering is 1-3°C / min, the target temperature of the sintering is 1200-1600°C, and the holding time after reaching the target temperature is 0.5-3h; The rare earth slurry in step (2) comprises ytterbium oxide, samarium oxide, neodymium oxide, praseodymium oxide, silicon dioxide, carboxymethyl cellulose and water; The mass ratio of ytterbium oxide, samarium oxide, neodymium oxide, praseodymium oxide, silicon dioxide, carboxymethyl cellulose and water is 22-26:20-22:19-21:19-21:10-20:0.5-1:23-46; The heating rate of the sintering in step (3) is 2-5°C / min, the target temperature of the sintering is 1300-1600°C, and the holding time after reaching the target temperature is 1-5h.

2. The preparation method according to claim 1, characterized in that The polycarboxylate is ammonium polycarboxylate; The average particle size of silicon carbide is ≤70 μm, the average particle size of silicon powder is ≤0.5 μm, the average particle size of elemental silicon is ≤50 μm, the average particle size of phenolic resin is ≤80 μm, the average particle size of iron oxide is ≤50 nm, and the average particle size of graphite is ≤20 μm.

3. The preparation method according to claim 2, characterized in that: The average particle size of the ytterbium oxide, samarium oxide, neodymium oxide and praseodymium oxide is ≤1 μm, and the average particle size of silicon dioxide is ≤10 μm.

4. The preparation method according to claim 3, characterized in that: The vacuum degree of the immersion in step (2) is 1000-2800 Pa, and the immersion time is 15-40 minutes.

5. The silicon carbide porous ceramic obtained by the preparation method according to any one of claims 1 to 4.

6. Application of the silicon carbide porous ceramics according to claim 5 in porous media combustion technology.

Citation Information

Patent Citations

  • Preparation method of high-strength silicon carbide porous ceramic

    CN102503521A

  • Hierarchical-pore silicon carbide porous ceramic for high temperature flue gas filtration and preparation method thereof

    CN110935237A

  • Silicon carbide-based composite foamed ceramic of multilayer hole rib structure and preparation method thereof

    CN105541334A

  • Process for manufacturing a ceramic composite material part by pressurized injection of a loaded slurry into a porous mould

    CN108779033A

  • Rare earth oxide modified silicon carbide ceramic based composite material and preparation method thereof

    CN110407597A